Development of environmental sustainability handout based on STEM-PjBL integrated islamic values - Abdullah, Zuhair; Dyah Kusumawati, Putri Rahadian; Khofifah, Ani; Laelatun Ni’mah, Nur Afina (Universitas Islam Negeri Sumatera Utara, 2024)
To holistically develop students’ potential, educators must develop integrative-interdisciplinary teaching materials. Therefore, this research aims to create environmental sustainability material handouts based on Science, Technology, Engineering, and Mathematics and Project Based Learning (STEM-PjBL) integrated with Islamic values suitable for use. The researchers conducted this research from December 2022 to May 2023. This research is research and development. The research and development approach used is the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model developed by Dick and Carry. This research shows that the handout developed contains STEM and PjBL components for eco enzyme production project activities. The researchers added Islamic values in the sub-discussion titled Islamic values related to environmental preservation. This sub-discussion explains Al-Qur’an verses and hadiths related to environmental conservation, such as ar-Rum verse 41, al-A’raf verse 56, and hadiths about the virtues of planting trees. The handouts developed are also suitable for use. The validator for the handout gave the feasibility assessment, which determines this feasibility, which received a score of 4.2 and is included in the good category.